MANAJEMEN RESIKO BENCANA MELALUI KERJASAMA ANTAR DAERAH (STUDI TENTANG MANAJEMEN RESIKO BENCANA GUNUNG SLAMET) - Widodo, Agus Setio; Waskita, Jaka (PERMANA, 2014)
Simple observation of events for the disaster in Indonesia is almost always showed the same picture is a condition in which reactive attitude and spontaneous, unplanned as shown by society and government. There is a general tendency thatpeople do not know how to act or addressing disaster.Various indications of weakness in the area of disaster proof (evidence) is notoptimal management of disasters in Indonesia. When considered from a variety of weak cases penggelolaan disaster in Indonesia, it can be said that Indonesia is still not ready to face the events of large and medium scale disasters.Key issues formulated in this article are as: Why is necessary inter-regionalcooperation Mount Slamet disaster management?Keywords: inter-regional cooperation, Mount Slamet, disasterrisk management